Kepuasan kualitas produk dan pelayanan pemasaran produk teh “Gamboeng” - Muhamad Nuriman; Kralawi Sita (Research Institute for Tea and Cinchona, 2018)
The competition of tea business in domestic market is increasingly fierce, inevitably demanding Research Institute for Tea and Cinchona (PPTK) as a research and profit center that produces a variety of tea products (black tea, green tea, and white tea) with the